FALSAFAH PENDIDIKAN ISLAM: PEMIKIRAN TA’DIB SYED MUHAMMAD NAQUIB AL-ATTAS - Sahidah, Sahidah (Universitas Nurul Jadid, 2021)
This article would like to highlight Syed Naquib al-Attas’ ideas on ta’dib. The emphasis on adab which includes practice (‘amal) in education and the educational process is to make sure that knowledge (‘ilm) is being put to good use in people. To know how to put knowledge in which place is called wisdom (hikmah). By utilizing a critical reading, this author elaborates the signifince of ta’dib as one of the various model of education. Based on this model, it is supposed to be a good man will appear as the embodiment of excellence in conduct of the Holy Prophet